Pengaruh Penggunaan Teknologi Sebagai Media Pembelajaran Ipa Dan Kreativitas Guru Terhadap Prestasi Peserta Didik Di Mi Muhammadiyah Karanganyar - Sartini Sartini; Desilva Sindra; Andriani Chondro Retno; Masduki Masduki (Journal Innovation In Education, 2024)
With regard to the learning achievement of class VI students at MI Muhammadiyah Karanganyar, the aim of the research is to determine the potential influence of teacher creativity and the use of technology as a science learning medium. Questionnaires were used in this study to measure how much technology is used as a science education tool and to evaluate the creativity of teachers. To determine the effect of a treatment on the dependent variable, this research method uses quantitative research in the form of experiments. By being given the opportunity to become a sample, each member of the population is given the opportunity to be selected using random sampling techniques. Three hundred and fifty students, seventeen males and eighteen females, comprised the VIG class sample. In this research, student learning achievement (Y) is the dependent variable and two independent variables are used, namely teacher creativity (X2) and use of technology as a science learning medium (X1). This research uses two types of data, namely the average daily science assessment score and primary data in the form of a questionnaire with 35 respondents. Regression analysis and correlation tests are used in the data analysis process to assess the relationship between variables. At ϼ= 0.05, the research produces Tcount = 0.745 and Ttable = 0.444. Tcount > Ttable shows that Hₒ is rejected and H₁ is accepted based on standard criteria. Thus, the learning achievement of class VI MI Muhammadiyah Karanganyar students is influenced by the use of technology as a science learning medium and teacher creativity.